Comparison of the effectiveness of the methods of cultivation and selection of Strongilata larvae in goats’ feces - Корчан, Л. М.; Корчан, М. І. (Scientific Progress & Innovations, 2012)
The article presents a comparative assessment of cultivation and selection methods of gastrointestinal Strongilata larvae in the goats’ feces: according to A. Petrov, W. Gagarin – in depending on the feces moistening method; and cultivation and selection of animals’ helminths larvae by means of using polypropylene cups. The most effective, sanitary safe and economically profitable way of Strongilata larvae cultivation proved to be the method of polypropylene cups with moistured by Sulfanilamide solute (0.1 %) samples.